Prostate cancer screening in Portugal: prevalence and perception of potential benefits and adverse effects - Braga, R (2020)
Introduction: Opportunistic screening for prostate cancer has been widely used, though organized programs are not recommended. We aimed to estimate the prevalence of prostate cancer screening and the perception of potential benefits and harms of screening, among the Portuguese general population. Methods: A representative sample of Portuguese-speaking inhabitants in mainland Portugal was selected, using a stratified probabilistic sampling procedure; men above 40 were considered for analysis (n = 414). Data on sociodemographic characteristics, lifetime use and usual frequency of prostate cancer screening (prostate-specific antigen test or digital rectal examination) and perception of potential benefits and adverse effects of cancer screening were assessed using face-to-face interviews, by structured questionnaire. Results: The proportion of participants who reported having been submitted to prostate cancer screening at least once in their lifetime was 44.2% (95% confidence interval: 37.5–51.0; 13.8% only digital rectal examination, 12.2% only prostate-specific antigen test, and 18.2% digital rectal examination and prostate-specific antigen test). As potential benefits of cancer screening, the options “knowledge of not having the disease”, “earlier detection” and “more effective treatment” were selected by 55.8%, 12.9% and 31.3% of the participants, respectively. Regarding potential adverse effects, the most and least frequently identified were ‘anxiety while waiting for the results’ (55.1%) and ‘false negatives’ (38.0%), respectively. Conclusions: Almost half of the men between 40 and 79 years old declared that they have been screened for prostate cancer. Nearly one-third of the participants considered that reassurance of a negative result was the main potential benefit of screening, whereas most failed to identify the most frequent adverse effects.